Capital Structure and Corporate Performance: Evidence from Malaysia - Koptleuova, Veronika (2009)
The objective of the current research is to investigate the effect of capital structure on corporate performance using 40 Malaysian listed companies during 2001-2008. Panel data analysis is used to investigate the relations between five measures of capital structure and corporate performance. Using various measurements of corporate performance, the results of this study suggest that firm’s capital structure has a significant negative impact on the firm’s accounting performance which indicates that agency cost problem can affect Malaysian companies followed by high debt policies, consequently resulting in lower firm performance. However, results also suggest that all capital structure ratios except short-term debt ratio have significant positive influence on market performance measurements, which indicates that capital structure and firm performance depend on rising share prices that affect positively on firm’s market performance ratio. The main value of this study is the analysis of the impact of various capital structure measures on corporate performance of Malaysian companies.